Sports Psychology: Mental Resilience and Performance in Elite Athletes - Lars Petersen (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Sports psychology explores the complex relationship between the human mind and athletic performance, making it a dynamic and vital aspect of the quest for athletic success. An overview of the many uses of sports psychology is given in this research, with a focus on how it may improve mental toughness, maximize performance, and promote the overall growth of athletes. The applications cover a wide range of topics, including youth development, team dynamics, injury recovery, and individual mental skills training. For measuring the research used smart PLS software and generate results included descriptive statistic, correlation coefficient and smart PLS Algorithm model of each indicator. Sports psychologists help athletes navigate pressure, failures, and transitions by establishing mental toughness, which serves as a cornerstone and provides the psychological fortification required for long-term success. Goal-setting and intrinsic motivation are crucial, and sports psychologists collaborate with players to help them develop a love for their activity and create attainable but difficult objectives. Beyond the individual, the nuances of team dynamics, effective communication, and leadership development are covered. Sports psychology has an influence on more than just the competitive field; it also has an impact on injury recovery, since psychological support is essential to an athlete's return to top performance. Furthermore, the discipline influences the roles of parents and coaches, instills vital life skills, and fosters a pleasant sports environment, all of which help to grow young people. Overall research founded that positive and significant relation between sport psychology related to mental resilience and performance in elite athletes. Overall research founded that effectively captures the transformational potential of sports psychology as a force for change that extends beyond the realm of physical sports. The cooperative endeavours of players, coaches, and sports psychologists shed light on a route towards adaptability, development, and long-term achievement in the ever-changing realm of sports.